A glimpse into the black box of celiac disease complications: a case report with a rare presentation - Natalya Viktorovna Rylova; Ahmed Arafat; Almazia Raisovna Shakirova; Ilyuza Shaidullina; Rozaliya Zakirova (Gastroenterology Review)
The purpose of this article is to report a case of celiac disease in a child with uncommon presentation and severe complica tions, and briefly review recent literature regarding celiac disease complications in children. We describe a case report of celiac disease in a child (to our knowledge, this is the first to be reported in its unique presentation in the Russian Federation) and precisely review its presenting complications with the exiting works of literature. Many cases of celiac disease in children who are not diagnosed and treated properly suffer from a plethora of complications due to malabsorption and concurrent autoimmune reactions that affect mainly but are not limited to the endocrine system. Complications of celiac disease in children should always be suspected, and evidence-based follow-up recommendations should be introduced as soon as possible because the burden of celiac disease complications in children is remarkable.